Assessing impacts of introducing ship‐to‐store service on sales and returns in omnichannel retailing: A data analytics study - Serkan Akturk, M.; Ketzenberg, Michael; Heim, Gregory R. (Journal of Operations Management, 2018)
Omnichannel retailing features, such as ship‐to‐store (STS) service, are designed to deliver a seamless shopping experience for customers. For a retailer, introducing omnichannel capabilities requires major investments to integrate physical stores and online marketplaces, yet holds a promise of potentially enhancing revenue streams from both brick‐and‐mortar (BM) stores and online store channels. We assess the promise of ship‐to‐store capabilities by analyzing transactional data from a national jewelry retailer to study impacts of introducing ship‐to‐store on a retailer's operating performance, in terms of sales and customer returns. Contrary to expectations, the findings show that online sales decreased after ship‐to‐store was introduced, although BM store sales increased. Detailed analysis of the transactional data suggests that, after STS implementation, some customers switched from the online channel to the brick‐and‐mortar channel. This switch occurred mainly for high‐value purchases. The customers who actually remained with and fully completed a sale using the ship‐to‐store service typically were those that bought low‐value items. Our findings also suggest that introducing ship‐to‐store increased cross‐channel customer returns of online purchases to physical stores. Concurrently, these new ship‐to‐store returns generated additional BM store sales. The paper contributes by showing how introducing ship‐to‐store service can have different impacts in terms of sales and returns across a retailer's channels.